The impact of digital networking on the life of asylum seekers in Italy. Issue 2 (1st October 2018) - Pischetola, Magda; Sozzani, Clio
The article aims to investigate the relation between migration and digital technologies, in particular the way in which connectivity contributes to new forms of social inclusion. The study presented explores asylum seekers' digital connections in relation to affective belonging, focusing on how social media enhance new forms of relationship between the homeland and host countries, as well as across migration flows. The research draws from the humanities and social sciences, proposing a qualitative methodology based on in-depth interviews with five migrants from the Middle East and Africa, who are hosted in a temporary camp for asylum seekers in Italy. It focuses on the way in which they remain connected to their home countries and how they try, at the same time, to create new relationships in the host country. The results outline how different forms of communication and digital networking impact on the migrants' settling into new lives at the local and transnational level.